2021
DOI: 10.33541/mk.v36i3.3361
|View full text |Cite
|
Sign up to set email alerts
|

Beban Candida dalam Saluran Cerna Anak

Abstract: AbstrakMikrobiota terbesar pada tubuh manusia terdapat pada saluran cerna (70%).Mikrobiota normal saluran cerna tersusun atas komposisi mikroorganisme yang unik dan berada dalam keadaan seimbang, didalamnya termasuk Candidaspp., yang hidup sebagai komensal. Data tentang keberadaan Candida dalam usus terutama berasal dari orang dewasa, sedangkan data pada anak sangat jarang. Penelitian ini bertujuan untuk mengetahui keragaman spesies Candida dan bebannya pada saluran cerna anak. Untuk menghitung beban jamur, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…C. albicans is a species pathogen that will proliferate at temperatures between 25-37 °C. 29 The C. albicans detachment process, which is essential for biofilm formation, is also thought to occur before the biofilm formation process. 6,18 Solvent plays an essential function in this research as a biocatalyst, such as substrate biotransformation or carrier substrate phase, making it easier to observe biofilm formation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans is a species pathogen that will proliferate at temperatures between 25-37 °C. 29 The C. albicans detachment process, which is essential for biofilm formation, is also thought to occur before the biofilm formation process. 6,18 Solvent plays an essential function in this research as a biocatalyst, such as substrate biotransformation or carrier substrate phase, making it easier to observe biofilm formation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the treatment groups that were given sulfated polysaccharides or simvastatin were able to decrease triglyceride levels. This is because in addition to increasing HDL levels and reducing total cholesterol levels in the blood, simvastatin can also reduce triglyceride levels [30]. The same held true for the sulfated polysaccharides [22,31].…”
Section: Triglyceride Levelsmentioning
confidence: 91%
“…These results indicate that the treatment groups that were given simvastatin and sulfated polysaccharides had an effect in the form of a decrease in total cholesterol levels. This is because simvastatin is a statin class drug which is the first line of defence in reducing total cholesterol levels in the blood [30]. Regarding the previous research, it is showed that sulfated polysaccharides have a better effect than simvastatin in reducing total cholesterol levels [22,31].…”
Section: Total Cholesterol Levelsmentioning
confidence: 96%
See 1 more Smart Citation